Redefining British policy at the beginning of the Cold War: South-East Europe in London's foreign policy strategies - Alexandru D. Aioanei (CES Working Papers, 2021)
Great Britain played a significant part in the endeavours directed at organizing the peace process in the aftermath of the Second World War. A series of myths were consequently associated to its actions and foreign policies-related decisions, myths that still surface to the present day in some areas, especially with regard to London's attitude towards Eastern-European countries. Our study proposes a more nuanced approach of the events of the first post-war years, focusing primarily on the impact the domestic situation of the Empire had upon its foreign policy decisions. Our research is based on the recent contributions of several British and Eastern-European researchers who shed new light on Great Britain's attitude towards South-Eastern Europe. Our study discusses the factors that influenced the foreign policy decisions taken by London with regard to that region, by attempting to analyse the general framework from less explored perspectives.
Keywords: 330; British foreign policy; Cold War; Eastern Europe; Ernest Bevin